Dufour and radiation effect on MHD boundary layer flow past a wedge through porous medium with heat source and chemical reaction - Pattnayak, Hadibandhu; Mohapatra, Rojali (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Magnetohydrodynamics (MHD) boundary layer flow past a wedge with the influence of thermal radiation, heat generation and chemical reaction has been analyzed in the present study. This model used for the momentum, temperature and concentration fields. The principal governing equations is based on the velocity in a nanofluid and with a parallel free stream velocity and surface temperature and concentration. The governing nonlinear boundary layer equations for momentum, thermal energy and concentration are transformed to a system of nonlinear ordinary coupled differential equations by using suitable similarity transformation with fitting boundary conditions. The transmuted model is shown to be controlled by a number of thermo-physical parameters, viz. the magnetic parameter, buoyancy parameter, radiation conduction parameter, heat generation parameter, Porosity parameter, Dufour number, Prandtl number, Lewis number, Brownian motion parameter, thermophoresis parameter, chemical reaction parameter and pressure gradient parameter. Numerical elucidations are obtained with the legendary Nactsheim-Swigert shooting technique together with RungeKutta six order iteration schemes.